A Critical Review on Economical and Sustainable Solutions for Wastewater Treatment Using Constructed Wetland - Vishwakarma, Smily; Dharmendra, Dr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pollutant removal by the mechanism of constructed wetland has led to low cost, highly efficient wastewater treatment technology. Constructed wetlands (CWs) are artificial engineered systems that mimic like natural wetlands. CW`s have been used in previous research to treat a broad range of waste streams at large-scale for low-cost application in wastewater management.
Keywords: wetlands; artificial wetlands; wastewater treatment; low-cost technology; tereny podmokłe; sztuczne tereny podmokłe; oczyszczanie ścieków; technologia niskokosztowa